2015
DOI: 10.3945/ajcn.115.114660
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing eating patterns: a comparison of eating occasion definitions

Abstract: Different approaches to the definition of EOs affect how eating patterns are characterized, with the neutral definition best predicting variance in total energy intake. Further research that examines how different EO definitions affect associations with health outcomes is needed to develop consensus on a standard EO definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 38 publications
2
86
0
1
Order By: Relevance
“…This definition of EO has been shown to predict variance in total EI and measures of adiposity more strongly than applying EO definitions with no energy criterion (26,27) or differing time intervals (16,27). The EI from EOs within each hour of the day was examined and averaged across the 2 d of dietary recalls.…”
Section: Eosmentioning
confidence: 99%
“…This definition of EO has been shown to predict variance in total EI and measures of adiposity more strongly than applying EO definitions with no energy criterion (26,27) or differing time intervals (16,27). The EI from EOs within each hour of the day was examined and averaged across the 2 d of dietary recalls.…”
Section: Eosmentioning
confidence: 99%
“…The classification of temporal distribution of meals is usually based on cultural norms (67,68) . Recent analysis by Leech et al showed in an Australian survey that a neutral definition (individual eating occasions separated by a specific time interval, such as 15 min) was best in predicting variance in total energy intake (69) . A review by found that most studies included in their review use a participant-identified approach (70) .…”
Section: Food For Thoughtmentioning
confidence: 99%
“…Currently there are few studies which have investigated eating time patterns. Leech (2) investigated temporal eating habits in Australian adults using Latent Class Analysis(LCA). Here we use LCA to investigate the hourly eating patterns of UK adults.…”
mentioning
confidence: 99%
“…We investigated whether latent class membership was associated with age, BMI, working hours, living with other people, being married and household income. The association between age and class was assessed using an F Test and the association between other factors and latent class was assessed using a chi (2) test.…”
mentioning
confidence: 99%